Waterborne Cu exposure increased lipid deposition and lipogenesis by affecting Wnt/β-catenin pathway and the β-catenin acetylation levels of grass carp Ctenopharyngodon idella. (August 2020) - Xu, Yi-Chuang; Xu, Yi-Huan; Zhao, Tao; Wu, Li-Xiang; Yang, Shui-Bo; Luo, Zhi
Abstract: Lipid metabolism could be used as a biomarker for environmental monitoring of metal pollution, including Cu. Given the potential role of the Wnt/β-catenin signaling pathway and acetylation in lipid metabolism, the aim of this study was to investigate the mechanism of Wnt signaling and acetylation mediating Cu-induced lipogenesis. Grass carp Ctenopharyngodon idella, widely distributed freshwater teleost, were used as the model. We found that waterborne Cu exposure increased the accumulation of Cu and lipid, up-regulated lipogenesis, suppressed Wnt signaling, reduced β-catenin protein level and its nuclear location, reduced the sirt1 mRNA levels and up-regulated the β-catenin acetylation level. Further investigation found that Cu up-regulated lipogenesis through Wnt/β-catenin pathway; Cu regulated the β-catenin acetylation, and K311 was the key acetylated residue after Cu incubation. SIRT1 mediated Cu-induced changes of acetylated β-catenin and played an essential role in nuclear accumulation of β-catenin and Cu-induced lipogenesis. Cu facilitated lipid accumulation via the regulation of Wnt pathway by SIRT1. For the first time, our study uncovered the novel mechanism for Wnt/β-catenin pathway and β-catenin acetylation levels mediating Cu-induced lipid deposition, which provided insights into the association between Cu exposure and lipid metabolism in fish and had important environmental implications for monitoring metal pollution in the water by using new biomarkers involved in lipid metabolism. Graphical abstract: Image 1 Highlights: Cu exposure increased lipid deposition and up-regulated lipogenesis of grass carp. Wnt/β-catenin signal and its acetylation mediated Cu-induced change of lipogenesis. SIRT1 mediated Cu-induced change of β-catenin acetylation and its localization. Cu facilitated lipid accumulation via the regulation of Wnt signaling by SIRT1.